Rupture Characteristics of Large Earthquakes - Ye, Lingling (eScholarship, University of California, 2015)
The occurrence of many large and/or destructive global earthquakes over the past ten years has provided unprecedented seismic, geodetic, and tsunami recordings that reveal complex rupture processes advancing our understanding of earthquake physics. This thesis research has focused on seismological analysis of recent large earthquakes to extract observational insights that address two fundamental questions, “how do great earthquake rupture?”, and “what controls large earthquakes?”. We approach these two questions by providing an improved seismological understanding of large earthquake rupture processes, exploring the variation of kinematic source parameters, and placing the ruptures into the context of tectonic plate motions that drive the deformation.Given the great diversity of earthquakes, various seismic tools have been explored to give a better robust characterization of large earthquake ruptures. It includes W-phase point source inversion, back projection of seismic array data to map the space-time distribution of high-frequency coherent seismic radiation, determination of broadband source spectra and radiated energy, waveform inversion for co-seismic finite-source slip distribution, and forward modeling of and joint inversion with tsunami and GPS data. By applying these methods, I have studied large events located in different areas, including 1) megathrusts (subduction zone plate boundaries) along the Japan trench, Middle American Trench, and globally; 2) the large transform fault boundary near Scotia-Sea-Antarctic plate boundary, and 3) intraplate events in subducted slabs near the Philippine trench, at intermediate depth (70-300 km) beneath Rat Island earthquake and in the mantle transition zone (300-700 km) beneath Sea of Okhotsk and Ogasawara Islands. The controlling parameters for earthquake-related hazards (e.g. tsunami and strong ground shaking) and earthquake physical mechanisms (e.g. brittle failure, thermal weakening process, stress transfer) have been investigated with an emphasis on the frequency-dependence seismic radiation.